Development and validation of a RP-HPLC method for the quantization studies of ivermectin in solutions dosage forms - Elena Gabriela Oltean; Nica A. (Medicamentul Veterinar, 2011)
An isocratic high–performance liquid chromatography (HPLC) procedure was developed for quantitative determination of ivermectin in solutions dosage forms. HPLC separation was carried out by reversed phase chromatography KROMASIL C18 (150 mm x 4.6 mm i.e.; 5 μm particle size), held at 25°C. The mobile phase consisted of methanol/ water (90/ 10 v/ v), run at flow rate of 1 mL/min and with UV detection at 254 nm. Method validation investigated parameters such as linearity (r2 = 0.9999), range, precision, accuracy, specificity, limit of detection and limit of quantification. The described method can be successfully applied for the analysis of solutions dosage forms.